Research of the Optimization Design of the Inter-axle Differential of Large Power Transfer Case - Zhang Lei; Shan Hongbo; Ge Kai; Mu Lianhao; Zhang Bin; Gao Lili; Zhang Qing; Ji Minglu (Jixie chuandong)
The inter- axle differentials as a core component of power transfer cases is used to achieve the distribution of chassis power and meet the needs of working conditions of vehicle cornering and climbing,which has played a key role in ensuring the reliability of the vehicle power transmission. By using the two- stage optimization method,the inter- axle differential planetary wheel structure optimized design is carried out,on the one hand to ensure the strength of the structure,on the other hand to reduce the quality of products to meet the requirements of the vehicle light weight and high maneuverability. By the checking of classic strength calculation and finite element method,it shows that the optimization program could meet the requirements of both high torque and high- reliability design of the planetary gear inter- axle differential of multi- axis ultra- heavy-duty chassis large power transfer case.